HUBUNGAN PENGETAHUAN IBU TENTANG GIZI BALITA DENGAN STATUS GIZI BALITA DI PUSKESMAS BOTANIA KOTA BATAM TAHUN 2017 - Susanti Susanti (Ensiklopedia of Journal, 2018)
The nutritional issue in children is seen as a multifaceted problem since it is not only because of the economic status of the family, but also relates to the attitude, knowledge levels, as well as behavior of the children parents. The occurrence of the children nutritional problem in Botania Health Center in 2016 reported happen to 583 out of 10,712 children which covers 17.2% of the total suffered from malnutrition and considered have bad nutritional status. The purpose of this research is to investigate the mothers knowledge levels and their under-five year children nutritional status. This research is an analytic survey study with cross sectional approach. The study was conducted in August 2017. By employing accidental sampling technique, 40 mothers of 1 to 5 year children were selected as the sample. The data analysis used to test the data is Chi-Square statistical data. At this point, the Chi-Square test ensues score of p=0.00